First reports of Zoophthora radicans (Entomophthoraceae) and Metarhizium rileyi (Clavicipitaceae) as pathogens of Plutella xylostella (Lepidoptera: Plutellidae) in Argentina - Manfrino, Romina Guadalupe (2018)
Plutella xylostella (L.), diamondback moth (DBM), is considered among the 20 most resistant arthropods in the world. Entomopathogenic fungi are important mortality factors of Lepidoptera in the field. However, in Argentina entomopathogenic fungi as mortality factors of P. xylostella have not been identified. The aim of this study was to identify and isolate fungal pathogens of Plutella xylostella in Santa Fe, Argentina. The prevalence and seasonality of fungal infections were also investigated. Zoophthora radicans (Bref.) A. Batko (Entomophthoromycota: Entomophthorales) and Metarhizium rileyi (Farl.) Kepler, Rehner & Humber (Ascomycota: Hypocreales) as fungal pathogens of Plutella xylostella L. are reported for the first time in Argentina. The pathogens were identified from larvae, pupae and adults of P. xylostella on cauliflower and on cabbage. Zoophthora radicans was the predominant fungal pathogen, while M. rileyi was recorded from only one infected larva.